Sustainable mobility and beauty of public space - Luciana Mastrolonardo (Vitruvio: International Journal of Architectural Technology and Sustainability)
The quality of built environment is linked to the space in-between buildings and considers its formal, environmental and use values, due to specific needs for care and project re-appropriation. Sustainable mobility, a strategic objective of the European Union, cannot ignore the quality of the public space. The New European Bauhaus draw a new strategical attention to the critical role the quality of spaces plays in building a better world. The definition of space for active mobility as environmental islands, sidewalks, pedestrian areas, cycle paths or green ways, must follow morphological, functional and organizational needs. The beauty of the space starts from a new language of the street, through qualifying the places and avoiding a passive crossing for the transport logic, but satisfying a need that goes beyond our material dimension and is inspired by creativity and culture. This qualification is represented here in the case study of an Italian Biciplan as a sector plan able to build inclusive and accessible physical spaces for the community. The lack of attention of technicians in the execution of public works leads to reconsider the importance of these issues also in education and training. The fragmentation of technological knowledge must be recalibrated to provide useful tools without forgetting the quality and the overall beauty of the places when street language improve, also for cultural reason.